AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL 96% DAUN SEPAT (Mitragynaspeciosa) DAN DAUN DADANGKAK (Hydrolea spinosa L.) - Rakhmadhan Niah; Dwi Rizki Febrianti; Novia Ariani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Sepat leaaf (Mitragynaspeciosa) and dadangkak leaf (Hydrolea spinosa L.) are native plants of South Kalimantan. These plants have high phenolic and flavonoid content. The content of these secondary metabolites is thought to have antioxidant activity. Phenolic compounds and flavonoids work through free radical scavenging mechanisms and reduce oxidative stress. The purpose of this study was to determine the antioxidant activity of sepat leaf and dadangkak leaf using the DPPH (1,1-diphenyl-2picrylhydrazyl) method. Sepat and dadangkak leaf extracts were prepared by maceration method using 96% ethanol as a solvent. The extract obtained was tested for antioxidant activity using the DPPH (1,1-diphenyl-2picrylhydrazyl) method. The results showed that the antioxidant activity was very strong (<50 ?g / mL) in the ethanol 96% extract of sepat leaf with a value of 39.04 ?g / mL and the ethanol extract 96% of dadangkak leaf with a value of 41.84 ?g / mL.